Understanding Of E-Performance Program to Employee - Rachmansyah, Rizqi; Usrotin Choiriyah, Ilmi (Indonesian Journal of Public Policy Review, 2022)
Performance appraisal plays an important role for organizations because it allows organizations to know, measure and assess employee performance. The results of the performance appraisal help the organization to make decisions in the management of the organization's human resources. Performance appraisal is very influential on the effectiveness of the employee's work. Performance appraisal is seen as an assessment of the performance or work ability shown by employees in carrying out their duties and functions in accordance with work targets. In addition, the purpose of this study was to determine the effectiveness of the e-performance system in Sidokumpul Village, Sidoarjo District, Sidoarjo Regency.This study uses the theory of effectiveness. The method used in this research is descriptive qualitative research method with purposive sampling informant determination technique, namely the user of the e-performance system of employees in Sidokumpul Village, Sidoarjo District, Sidoarjo Regency. Data collection techniques in the form of interviews, observation, documentation. As well as data analysis techniques, namely data collection (data collection), data reduction (data reduction), data presentation (data display) and drawing conclusionsThe results of this study indicate that the e-performance system in Sidokumpul Village, Sidoarjo District, Sidoarjo Regency is still not effective. This is because there are several inhibiting factors, such as Sidokumpul sub-district employees who do not understand optimally about the operationalization of e-performance infrastructure, causing them to be less effective in reporting their duties. In addition, the operation of the e-performance system itself still has many obstacles, such as the internet network and the level of security that is not perfect.